Sanitary hygienic conditions of food services in Brazil: an integrative review (Research, Society and Development, 2020)
The purpose of this review was to evaluate the scientific production related to sanitary hygienic conditions in food services in Brazil. The Databases used in the research: Scielo, Lilacs, and PubMed, with the search for scientific productions from 2013 to 2018. Inclusion criteria: complete scientific publications, addressing the themes of food hygiene, good practices in food services, prepared and published in national territory, with Portuguese language. Exclusion criteria were scientific productions published outside the established period, literature reviews, international publications, theses, dissertations, editorials, epidemiological bulletins and letters to the editor. 33 articles were found in the research, but only 24 met the eligibility criteria. There was a considerable increase in scientific production in the North and Northeast regions. However, there was an increase in non-conformities in relation to the knowledge of good practices on the part of the handlers, insufficient inspection in the establishments, greater conformity in relation to the facilities and equipment hygiene and a greater number of non-conformities in relation to the required legal documentation and mandatory records. . The number of publications covering the topic of hygiene and sanitary surveillance of food services has been growing in Brazil, making it necessary to intervene based on published studies so that the number of conformities is more and more adequate to RDC no. 216/2004, thus aiming at a considerable reduction of contamination risks. There is a need for frequent inspection of the bodies responsible for registrations and other legal documentation necessary for the active operation of food service establishments in the country.